Postoperative aspirin use and its effect on bone healing in the treatment of ankle fractures. Issue 2 (February 2020) - Hunter, Allison M.; Montgomery, Tyler P.; Pitts, Charles C.; Moraes, Leonardo; Anderson, Matthew; Wilson, John; McGwin, Gerald; Shah, Ashish
Highlights: Post-operative Aspirin administration was non-inferior to no Aspirin after ankle fracture fixation in time to healing and radiographic union. Post-operative deep vein thrombosis was not significantly different between Aspirin and no Aspirin after ankle fracture fixation. Non-steroidal anti-inflammatories may be a reasonable choice for venous thromboembolism prophylaxis after ankle fracture fixation. Abstract: Background: There is hesitancy to administer nonsteroidal anti-inflammatories (NSAIDs) within the postoperative period following fracture care due to concern for delayed union or nonunion. However, aspirin (ASA) is routinely used for chemoprophylaxis of deep vein thrombosis (DVT) and is gaining popularity for use after treatment of ankle fractures. The current study examines the incidence of nonunion of operative ankle fractures and risk of DVT in patients who did and did not receive postoperative ASA. Methods: A retrospective chart review was performed on all patients treated between 2008 and 2018 for ankle fractures requiring operative fixation by three Foot and Ankle fellowship trained orthopaedic surgeons at a single institution. Demographics, preoperative comorbidities, and postoperative medical and surgical complications were compared between patients who did and did not receive ASA postoperatively. For both groups, union was evaluated by clinical exam as well as by radiograph, for those with 6-week, 12-week, or 24-week follow-up. Results: Five-hundred and six patients met inclusion criteria: 152 who received ASA and 354 who did not. Radiographic healing at six weeks was demonstrated in 95.9% (94/98) and 98.6% (207/210) respectively ( p -value .2134). There was no significant difference in time to radiographic union between groups. The risk of postoperative DVTs in those with and without ASA was not significantly different (0.7% (1/137) vs 1.2% (4/323), respectively; p -value .6305). Conclusion: Postoperative use of ASA does not delay radiographic union of operative ankle fractures or affect the rate of postoperative DVT. This is the first and largest study to examine the effect of ASA on time to union of ankle fractures. Level of Evidence: III